1999
DOI: 10.1021/ma980818t
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Peptide and Polypeptide Systems. 13. Photoinduced Cross-Linked Gel and Biodegradation Properties of Copoly(l-lysine) Containing ε-7-Coumaryloxyacetyl-l-lysine Residues

Abstract: Copoly[LysLys(Cou)] containing -7-coumaryloxyacetyl-L-lysine [Lys(Cou)] residues were synthesized by the N-carboxyanhydride method. When the aqueous solutions of copoly[LysLys(Cou)] containing 5-10 mol % of Lys(Cou) are irradiated by light, the photo-cross-linking reaction proceeds slowly between coumarin moieties in the side chains to give a cis head-to-head cyclocoumarin, and after 6-24 h the solutions become transparent hydrogels. The gels exhibit solvent-induced reversible expansion and contraction behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…The results themselves are scientifically interesting and might offer some clues towards the understanding of biological counterion interaction such as blood and extracellular material systems, as well as understanding its biomimesis, which undoubtedly includes a protein and/or polysaccharide interaction process, together with biodegradation by microorganisms and enzymes 15,[30][31][32] involved in keeping both land and sea ecology clean.…”
Section: Discussionmentioning
confidence: 99%
“…The results themselves are scientifically interesting and might offer some clues towards the understanding of biological counterion interaction such as blood and extracellular material systems, as well as understanding its biomimesis, which undoubtedly includes a protein and/or polysaccharide interaction process, together with biodegradation by microorganisms and enzymes 15,[30][31][32] involved in keeping both land and sea ecology clean.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies found that the rate of biodegradation of both polymers by enzymes (trypsin or protease type XXIII) or by soil fungi was controlled by the ratio of coumarinated to native protein and by the cross-link density of the polypeptides. 176,182 Matsuda and co-workers synthesized 4-arm stars based on random copolymers of -caprolactone (CL) and trimethylene carbonate (TMC) and subsequently endcapped the arms at the hydroxyl terminus with coumarin groups (poly(CL/TMC)). [172][173][174][175]197 The chemical structure of the stars is shown in Figure 29.…”
Section: Biomaterialsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Functionalities on the basis of the helical structure of polyamino acid derivatives are of great interest from biotechnological points of view. However, peptide mimics are not always as good as the expectation for the synthetic polymers, probably due to the lack of organized ternary structure of the polymers employed as functional materials.…”
Section: Introductionmentioning
confidence: 99%